El nuevo sistema de control de concentraciones empresariales en Perú a la luz de la experiencia chilena - Alliende Serra, Macarena (2020)
Law 31112 contemplates the creation of an unprecedented mandatory preventive merger control in Peru, which will come into force within 15 days after the publication of the adaptation that Indecopi must elaborate.The institutional design of the Peruvian merger control system has several similarities with the Chilean system, which was implemented through Law 20945 of 2016, and in force since June 1, 2017. The over 100 cases resolved by the Chilean competition authority have involved a relevant evolution in the criteria and tools applied. In this sense, given the similarity between both systems, the author presents how the Chilean experience can feed future discussions and practices of the neighboring jurisdiction, which could enhance coordination and cooperation between the two countries, improving the merger controls with effects across Latin America.